2017
DOI: 10.1002/adom.201601071
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐Butterfly‐Inspired Patterning of Helical Photonic Structures for Circular‐Polarization‐Sensitive, Wide‐Angle Diffuse Reflection

Abstract: Cholesteric liquid crystals are known to exhibit a circular-polarization selective Bragg reflection band over a wavelength region determined by their reflective index and pitch.In a planar device where the molecules are aligned unidirectionally at the substrate This article is protected by copyright. All rights reserved. 2 surface, cholesteric liquid crystals act as flat dielectric mirrors, reflecting light at an angle fulfilling the law of reflection. Here, we show that by introducing a random structure inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Morpho didius buttery-inspired cholesteric liquid crystals were used to demonstrate circular polarized light diffusion and the diffusion angle was limited between 80 and 100 . 2 However, in this study, we have demonstrated that Morpho peleides buttery wing scales embedded in PVA were used to modify the photonic bandgap and enable unpolarized light diffusion over a broad range (diffusion angle $185 ). A few drops of liquid PVA was poured in Morpho buttery wing scales.…”
Section: Optical Diffusion Based On Wing Scalesmentioning
confidence: 88%
“…Morpho didius buttery-inspired cholesteric liquid crystals were used to demonstrate circular polarized light diffusion and the diffusion angle was limited between 80 and 100 . 2 However, in this study, we have demonstrated that Morpho peleides buttery wing scales embedded in PVA were used to modify the photonic bandgap and enable unpolarized light diffusion over a broad range (diffusion angle $185 ). A few drops of liquid PVA was poured in Morpho buttery wing scales.…”
Section: Optical Diffusion Based On Wing Scalesmentioning
confidence: 88%
“…In the previous study, we performed patterned photoalignment based on maskless polarization lithography for device fabrication [6][7][8][9]. In maskless polarization lithogra-phy, a liquid crystal display (LCD) projector is used as an electronic mask and its output is projected on the sample after controlling its polarization; the photoalignment layer sets its orientational easy axis according to the polarization of the illuninated light.…”
Section: Experimental Methods Interference Exposure Setupmentioning
confidence: 99%
“…While metasurfaces are viewed as a platform that can eventually replace conventional, bulky optics, re ective metasurface elements are often *Corresponding Author: Hiroyuki Yoshida: Division of Electrical, Electronic and Information Engineering, Osaka University, 2-1 Yamadaoka Suita, Osaka 565-0871, Japan and PRESTO, Japan Science and Technology Agency (JST), 4-1-8 Honcho Kawaguchi, Saitama 332-0012, Japan, E-mail: yoshida@eei.eng.osaka-u.ac.jp Junji Kobashi, Yoshinori Mohri: Division of Electrical, Electronic and Information Engineering, Osaka University, 2-1 Yamadaoka Suita, Osaka 565-0871, Japan Masanori Ozaki: Division of Electrical, Electronic and Information Engineering, Osaka University, 2-1 Yamadaoka Suita, Osaka 565-0871, Japan, E-mail: ozaki@eei.eng.osaka-u.ac.jp opaque, limiting their usability [4,5]. Recently, we have reported re ection-type, circular-polarization sensitive planar optical elements based on cholesteric liquid crystals (ChLCs) [6][7][8][9]. ChLC is a LC phase in which rod-shaped molecules spontaneously form a helical structure, and shows Bragg re ection over a speci c wavelength range for circularly polarized light having the same helicity as the sense of the helical structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the relatively intuitional surface scattering of randomly textured dielectric interfaces [ 8 , 9 ], it was recently discovered that bulk scattering exists within inhomogeneous structure, which stems from cross-correlation parameters between roughnesses or inhomogeneities [ 10 , 11 ]. Consequently, a new branch of diffuse reflector emerges, which relies on a full exploitation of excitations and interferences of both surface and bulk scattering [ 12 , 13 ] and enables much more flexible control of both magnitudes and polarizations of the electromagnetic fields [ 14 , 15 ]. Moreover, such a field rapidly hybridizes with other branches of plasmonics, optical nanoantennas, and metamaterials, which renders enormous extra freedom for manipulations of various kinds of light-matter interactions and makes possible lots of novel photonic functionalities and devices [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is of great importance for various applications including solar cell, illumination, and many other applications related to light-matter interaction enhancement in devices [ 22 24 ]. Nevertheless, similar to many novel functionalities obtained in surface-relief structures and nanoparticle-based structures [ 16 24 ], the existing approaches to obtain diffuse reflector heavily rely on the excitations of the scattering of randomly textured surface [ 14 , 15 ]. Then it is vital to ask: Can the diffuse reflectors be supported by interface and bulk scattering simultaneously to realize better functionalities?…”
Section: Introductionmentioning
confidence: 99%